Fiber in Broiler Feed: Its Effect on Performance, Gastro-intestinal Tract, and Microbial Profile - Intan Nursiam; Muhammad Ridla; Nahrowi Nahrowi; Widya Hermana (Indonesian Center for Animal Research and Development, 2021)
In AGP ban era, addition of a fiber source in broiler feed improves the performance and development of the gastrointestinal tract. This paper aims to describe the differences in fiber analysis methods and the effect of fiber source addition on growth, development of the gastrointestinal tract, and microbiota profile in the digestive tract of broilers. Oat hulls, sugar beet pulp, rice hulls, pea hulls, sunflower hulls, wheat bran, and wood have been tested as fiber source in broiler feed. The effectiveness of fiber in increasing growth performance and stimulating the development of the gastrointestinal tract were influenced by the physico-chemical properties, level of addition, particle size, and fraction composition of the fiber source. Exploration of local fiber sources from Indonesia, which can have ability to increase growth performance and gastrointestinal tract development of broilers is needed to support food security in the future.